2019
DOI: 10.1016/j.jpcs.2018.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and magnetic characterization of Ni0.5Zn0.5Fe2O4 ferrite nanoparticles

Abstract: The comprehensive study of the Ni0.5Zn0.5Fe2O4 ferrite nanopowder crystallized in the inverse spinel structure and synthesized by co-precipitation method is presented. The distribution of Fe 3+ cations among tetrahedral and octahedral sites was confirmed. The microstructural investigations revealed the presence of ultrafine grained structure with an average crystallites size in the range of 14 ÷ 20 nm. Raman and Fourier-Transform Infrared (FTIR) spectroscopy studies confirmed typical spinel structure with tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(26 citation statements)
references
References 119 publications
(289 reference statements)
3
23
0
Order By: Relevance
“…Available data on the mechanism of the ferritization process suggests a rather complex phase composition of the sediments obtained. The sediment may contain various modifications of oxides and oxyhydrates of ferrum, nickel, copper, and zinc, which by nature are ferromagnetic, but, due to the small dimensions, they demonstrate paramagnetic properties [17]. Our analysis of structural studies has revealed that samples from the G2 and G7 series of experiments, obtained under the thermal and electromagnetic pulse activation technique, are, respectively, characterized by the maximal content of ferrite phases with magnetic properties (≥89 %).…”
Section: Discussion Of Results From Studying the Processing Of Galvanmentioning
confidence: 92%
See 1 more Smart Citation
“…Available data on the mechanism of the ferritization process suggests a rather complex phase composition of the sediments obtained. The sediment may contain various modifications of oxides and oxyhydrates of ferrum, nickel, copper, and zinc, which by nature are ferromagnetic, but, due to the small dimensions, they demonstrate paramagnetic properties [17]. Our analysis of structural studies has revealed that samples from the G2 and G7 series of experiments, obtained under the thermal and electromagnetic pulse activation technique, are, respectively, characterized by the maximal content of ferrite phases with magnetic properties (≥89 %).…”
Section: Discussion Of Results From Studying the Processing Of Galvanmentioning
confidence: 92%
“…Samples from the G2 and G7 series contain crystals of irregular shape in a porous space. Such structures have good sorption capacity both for heavy metal ions and to organic matter, and thus can be successfully used to clean flush waste water from industrial production [17]. The results from experiments, given in Table 4, showed that for galvanic sludge the content of heavy metal ions in the leaching eluate does not meet the requirements by DSanPiN 2.2.7.029-99 and the EU Directive 86/278/EU in terms of MPC in soil.…”
Section: Fig 3 Volume Of Compacted Sediments V C Obtained In the Prmentioning
confidence: 99%
“…[37][38][39] In our case, the higher frequency absorption band y 1 is assigned for Fe 3+ -O intrinsic vibration of tetrahedral group in the range of 570 cm À1 and the lower frequency absorption band y 2 is attributed to that of the octahedral group near 405 cm À1 which is the ngerprint of Zn-Ni ferrites. 39,40 There are additional frequency band located near 1061 cm À1 corresponding to the O-H stretching vibrations. 41 It can be noted from the gure that the peaks intensity amplies with raising the Nd 3+ doping level.…”
Section: Ftir Measurementsmentioning
confidence: 99%
“…According to Figure 5A, BaFe 12 O 19 mainly consist of agglomeration micro and nanoparticles. The aggregation is a result of magnetic dipole‐dipole interaction between nanoparticles 24 . Besides, based on Figure 5B‐G, the addition of substitutions increases their concentration from 0.25 to 1.5 causing agglomeration to decrease forming small nanoparticles.…”
Section: Resultsmentioning
confidence: 96%